Optimizing Systematic Land Registration (PTSL) to Enhance Legal Certainty of Land Ownership Rights: Collaboration with Religious Value in Indonesia - Zaenuddin, Fatahussalam; Zahra, Hemalia; Rahmayanti, Inka Febby (Religion and Policy Journal, 2024)
Research Problem: Land disputes between the public and various stakeholders frequently arise in Indonesia, often due to limited public trust in the Complete Systematic Land Registration Program (PTSL). This distrust results in low participation in PTSL, affecting land security and legal ownership. Research purposes: This study aims to analyze how religious institutions and values can help optimize PTSL to provide stronger legal guarantees for land ownership while supporting the legal protection of land rights within the community. Research methods: A qualitative approach with descriptive-analytical methods was applied to explore the relationship between PTSL implementation, public trust, and religious influence on land registration. Results and Discussion: The findings indicate that the implementation of PTSL has been effective in promoting land certification, which strengthens legal protection in compliance with existing laws. Moreover, the involvement of religious institutions has been shown to foster public trust by aligning PTSL with community values rooted in faith, making the program more widely accepted. Research Implications and Contributions: The research highlights the importance of religious institutions in enhancing public trust in government programs like PTSL. By integrating community beliefs into the implementation of PTSL, the program not only functions as a mechanism for legal protection but also aligns with ethical and religious principles. This study provides a conceptual foundation for the government to incorporate religious and community values into policy implementation, ultimately enhancing legal certainty and protection of land rights.